Organic adsorbent and method for producing the same

The organic adsorbent, composed of mineral particles coated with specific proteins and polysaccharides and irradiated with plasma, effectively addresses the challenge of removing perfluoroalkyl and polyfluoroalkyl compounds from the environment, offering high adsorption ability and safety for living organisms.

JP7671048B1Active Publication Date: 2025-05-01LUMILITE JAPAN CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024196193
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-05-01
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

There is a social concern regarding environmental pollution from organic fluorine compounds such as perfluoroalkyl and polyfluoroalkyl compounds, which require an adsorbent with high adsorption ability and safety for living organisms.

Method used

An organic adsorbent is developed using mineral particles coated with proteins and/or polysaccharides, specifically collagen, elastin, desmosin, or isodesmosin, and glycosaminoglycans, which are then irradiated with plasma to enhance adsorption capabilities.

Benefits of technology

The organic adsorbent exhibits a high adsorption ability, particularly for perfluoroalkyl and polyfluoroalkyl compounds, while being safe for living organisms, effectively removing these pollutants from water and soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671048000001_ABST
    Figure 0007671048000001_ABST
Patent Text Reader

Abstract

Provided is an adsorbent which has high adsorption capacity for organic matter and is highly safe for living organisms. [Solution] An organic matter adsorbent containing mineral particles as an active ingredient, wherein the surfaces of the mineral particles are coated with proteins and / or polysaccharides, and the proteins and / or polysaccharides are one or more selected from collagen, elastin, proteins containing desmosine or isodesmosine, and glycosaminoglycans, and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an organic matter adsorbent that contains mineral particles as an active ingredient and has a high adsorption capacity for organic matter such as organic fluorine compounds typified by perfluoroalkyl compounds and polyfluoroalkyl compounds, and a method for producing the same. [Background technology]

[0002] Materials for efficiently removing trace amounts of organic pollutants from the environment and pollutant removal technologies using such materials have been developed. For example, adsorbent materials treated with calcium, magnesium, strontium, or barium ions, salts, oxides, hydroxides, or carbonates (see Patent Document 1), and porous polymer materials containing multiple cross-linked cyclodextrins (see Patent Document 2) are known.

[0003] The inventors of the present invention have previously developed a water quality improvement treatment agent containing powder of natural porous ore (see Patent Document 3) and a water quality improvement treatment agent containing clinoptilolite, kaolinite, montmorillonite, etc. (see Patent Document 4). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2020 / 206317 [Patent Document 2] Patent No. 7403855 [Patent Document 3] Patent No. 4822369 [Patent Document 4] International Publication No. 2023 / 200046 Summary of the Invention [Problem to be solved by the invention]

[0005] Environmental pollution by organic pollutants, such as organic fluorine compounds, typified by perfluoroalkyl compounds and polyfluoroalkyl compounds, has become a social problem. Therefore, there has been a demand for an adsorbent that has a high adsorption capacity for these organic substances and is also highly safe for living organisms. [Means for solving the problem]

[0006] The present invention provides an organic adsorbent containing mineral particles as an active ingredient, in which the surfaces of the mineral particles are coated with proteins and / or polysaccharides, and the proteins and / or polysaccharides are one or more selected from collagen, elastin, proteins containing desmosine or isodesmosine, and glycosaminoglycans.

[0007] The organics may be organofluorine compounds, which may be perfluoroalkyl and polyfluoroalkyl compounds.

[0008] Another aspect of the present invention is an organic adsorbent, wherein the mineral particles are composed of one or more selected from clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, monazite, and bastnaesite, and the mineral particles contain one or more selected from light rare earth elements, neodymium, and dysprosium.

[0009] Another aspect of the present invention is an organic adsorbent, wherein the mineral particles are composed of clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, and monazite and / or bastnaesite.

[0010] Yet another aspect of the present invention is an organic adsorbent, wherein the surface charge of mineral particles is 0.05 mV to 0.1 mV.

[0011] The present invention provides a method for producing an organic adsorbent, comprising the steps of providing mineral particles, coating the surfaces of the mineral particles with a protein and / or a polysaccharide, and irradiating the coated mineral particles with plasma, wherein the protein and / or the polysaccharide is selected from collagen, elastin, a protein containing desmosine or isodesmosine, and a glycosaminoglycan.

[0012] The step of irradiating with plasma in the present invention may be a step of irradiating with plasma in a reducing atmosphere or in a substantially vacuum atmosphere. Effect of the Invention

[0013] The organic adsorbent obtained in the present invention exhibits extremely high adsorption capacity, particularly for organic fluorine compounds such as perfluoroalkyl compounds and polyfluoroalkyl compounds, and is highly safe for living organisms. [Brief description of the drawings]

[0014] [Figure 1] 1 is a scanning electron microscope image of the surface of an organic adsorbent produced in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention relates to an organic adsorbent containing mineral particles as an active ingredient and a method for producing the same. The present invention will be described in detail below based on the embodiments of the invention, but the present invention is not limited to the embodiments shown below.

[0016] The organic adsorbent of the present invention efficiently adsorbs organic fluorine compounds. The organic adsorbent of the present invention can efficiently adsorb perfluoroalkyl compounds and polyfluoroalkyl compounds, collectively known as PFAS, among organic fluorine compounds. The organic adsorbent of the present invention adsorbs PFAS contained in water and / or soil, thereby removing PFAS from the water and / or soil.

[0017] That is, the present invention relates to an organic adsorbent used for removing organic fluorine compounds, preferably perfluoroalkyl and polyfluoroalkyl compounds, from water and / or soil. The present invention also relates to an organic fluorine compound remover containing mineral particles as an active ingredient, and also relates to a perfluoroalkyl and polyfluoroalkyl compound remover, i.e., a PFAS remover.

[0018] The present invention contains mineral particles as an active ingredient. The mineral particles contained in the present invention are mineral particles whose surfaces are coated with proteins and / or polysaccharides. The proteins and / or polysaccharides used in the present invention are not limited as long as the mineral particles coated on the surfaces can efficiently adsorb organic matter, but in one embodiment, the proteins may be collagen, elastin, proteins containing desmosine or isodesmosine, etc., and the polysaccharides may be glycosaminoglycans.

[0019] The mineral particles contained in the present invention are mineral particles having a surface charge. The surface charge is preferably a positive surface charge. In one embodiment, the surface charge is 0.01 mV or more, and may be 0.01 mV to 1 mV, and may be 0.05 mV to 0.1 mV. Preferably, the surface charge may be a permanent or semi-permanent surface charge.

[0020] In one embodiment, the mineral particles which are an active ingredient in the organic adsorbent are composed of one or more minerals selected from clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, monazite, and bastnaesite.

[0021] Clinoptilolite, also known as clinoptilolite, is a naturally occurring silicate mineral and a type of zeolite. It has a microporous structure of silicon dioxide and alumina tetrahedrons and is known to be effective in removing active oxygen and pollutants.

[0022] Kaolinite is a type of silicate mineral, also known as kaolinite. Kaolinite is produced when feldspar such as granite is decomposed by weathering. The chemical formula of kaolinite is Al2Si2O5(OH)4, and it is a mineral with a layered structure in which silica tetrahedral layers and alumina octahedral layers are stacked.

[0023] Montmorillonite is a type of silicate mineral, also known as montmorillonite. Montmorillonite is found in rocks that have been subjected to hydrothermal alteration. It is characterized by its high swelling property. It has a 2:1 layered structure in which silica tetrahedral layers and alumina octahedral layers are alternately stacked, and it is known that it expands when moisture or cations get between the layers.

[0024] Laumontite is a type of silicate mineral also known as laumontite. Like montmorillonite, it has a 2:1 layer structure in which silica tetrahedral layers and alumina octahedral layers are alternately stacked, but the interlayer distance of laumontite is relatively small, and it is known to have low swelling properties.

[0025] Perlite is a general term for glassy volcanic rocks, and is a natural mineral composed mainly of silicon dioxide. It is known to be favorable for the attachment of microorganisms and organic matter because of its light weight and excellent porosity.

[0026] Quartz, also known as quartz, is a natural mineral whose main component is silicon dioxide. It is known for its excellent wear resistance, heat resistance, and chemical stability.

[0027] Pozzolan is a naturally occurring mineral rich in silicon dioxide, derived primarily from volcanic ash and other volcanic rocks. It is an important mineral used to improve the strength and durability of concrete and cement.

[0028] Makbanite is a natural mineral of volcanic origin, composed mainly of silicon dioxide and aluminum oxide with small amounts of iron oxide. It is porous and known to have a high ability to adsorb organic matter.

[0029] Monazite is a phosphate mineral also known as monazite, and contains rare earth elements such as cerium, lanthanum, yttrium, neodymium, samarium, and thorium. Together with bastnaesite, it can be contained in the mineral particles of one embodiment as a supply source of rare earth elements described later.

[0030] Bastnaesite is a carbonate mineral also known as bastnaesite, and contains rare earth elements such as cerium, lanthanum, neodymium, yttrium, samarium, and thorium. Together with monazite, it can be contained in the mineral particles of one embodiment as a supply source of rare earth elements described later.

[0031] In one embodiment, the mineral particles contain a rare earth element. Preferably, the rare earth element is one or more selected from cerium, lanthanum, neodymium, yttrium, samarium, thorium, and dysprosium, and these rare earth elements can be supported in the mineral particles by porous minerals such as zeolite, monazite, bastnaesite, and the like.

[0032] In one embodiment, the mineral particles contain light rare earths, which are lanthanoid elements having atomic weights less than that of gadolinium, specifically lanthanum, cerium, praseodymium, neodymium, promethium, samarium, and europium.

[0033] In one embodiment, the mineral particles contain neodymium and / or dysprosium. Neodymium and dysprosium are used as raw materials for magnets. These elements are known to have the function of adsorbing elements such as phosphorus in water and / or soil.

[0034] In one embodiment, the organic adsorbent comprises mineral particles composed of clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, and monazite and / or bastnaesite, containing neodymium and dysprosium.

[0035] In another embodiment, the organic adsorbent is composed of 65 to 75 parts by weight of clinoptilolite, 5 to 15 parts by weight of kaolinite, 3 to 10 parts by weight of montmorillonite, 1 to 3 parts by weight of laumontite, 1 to 3 parts by weight of perlite, 1 to 3 parts by weight of quartz, 5 to 9 parts by weight of pozzolan, 1 to 3 parts by weight of makbanite, and 0.05 to 0.2 parts by weight of monazite and / or bastnaesite, and contains mineral particles containing 0.005 to 0.02 parts by weight of neodymium and 0.005 to 0.02 parts by weight of dysprosium.

[0036] Furthermore, the mineral particles contained in the organic adsorbent of the present invention are mineral particles whose surfaces are coated with proteins and / or polysaccharides. The protein that coats the surface may be a protein containing collagen, elastin, desmosine or isodesmosine, and the polysaccharide that coats the surface may be glycosaminoglycan. Coating the surface of the mineral particles with proteins and / or polysaccharides can impart a remarkable ability to adsorb organic matter to the mineral particles.

[0037] In one embodiment, the organic adsorbent is composed of 65 to 75 parts by weight of clinoptilolite, 5 to 15 parts by weight of kaolinite, 3 to 10 parts by weight of montmorillonite, 1 to 3 parts by weight of laumontite, 1 to 3 parts by weight of perlite, 1 to 3 parts by weight of quartz, 5 to 9 parts by weight of pozzolan, 1 to 3 parts by weight of makbanite, and 0.05 to 0.2 parts by weight of monazite and / or bastnaesite, and contains 0.005 to 0.02 parts by weight of neodymium and 0.005 to 0.02 parts by weight of dysprosium, and contains mineral particles as an active ingredient, the mineral particles having a surface coated with one or more selected from 0.002 to 0.01 parts by weight of collagen, elastin, a protein containing desmosine or isodesmosine, and glycosaminoglycans.

[0038] Furthermore, the present invention provides a method for producing an organic adsorbent, comprising the steps of providing mineral particles, coating the surfaces of the mineral particles with a protein and / or a polysaccharide, and irradiating the coated mineral particles with plasma.

[0039] In one embodiment, the step of providing mineral particles provides mineral particles comprised of one or more selected from clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, monazite, and bastnaesite. In another embodiment, mineral particles containing one or more selected from light rare earths, neodymium, and dysprosium are provided. In yet another embodiment, the step of providing mineral particles provides mineral particles comprised of clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, and monazite and / or bastnaesite, and containing neodymium and dysprosium.

[0040] The mineral particles are prepared from pulverized raw materials obtained by pulverizing each raw material. The particle size of the pulverized raw materials is not limited, but may be one that passes through a 100 to 500 mesh or one that passes through a 300 to 400 mesh.

[0041] The mineral particles are prepared by calcining the mixed powder obtained by mixing the raw materials in a plurality of different temperature zones. In one embodiment, the mineral particles are prepared by a first heating step of heating the pulverized raw materials in a first temperature zone, a second heating step of heating the raw materials heated in the first heating step in a second temperature zone, and a third heating step of heating the raw materials heated in the second heating step in a third temperature zone. Here, the pulverized raw materials may be one or more selected from clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, monazite, bastnaesite, neodymium, and dysprosium.

[0042] In one embodiment, the first heating step may be a step of heating at 110 to 130° C. for 5 minutes, the second heating step may be a step of heating at 260 to 370° C. for 5 minutes, and the third heating step may be a step of heating at 410 to 470° C. for 5 minutes. Each heating step may be a step of heating the raw material while stirring it. In addition, after the end of each heating step, a cooling step of cooling the heated raw material to room temperature may be included.

[0043] The surfaces of the mineral particles prepared as described above are then coated with proteins and / or polysaccharides. The surface-coated mineral particles are obtained by stirring in the presence of the protein and / or polysaccharide powder and the prepared mineral particles. In one embodiment, the mineral particles are surface-coated by stirring with 0.0001-0.1 wt %, 0.001-0.01 wt %, or 0.002-0.0033 wt % of the protein and / or polysaccharide relative to the mineral particles.

[0044] In one embodiment, the protein may be collagen, elastin, a protein containing desmosine or isodesmosine, or the like, and the polysaccharide may be glycosaminoglycan. The protein and / or polysaccharide may be a powder obtained by freeze-drying them. In another embodiment, the protein and / or polysaccharide may coat the surface of the mineral particles in a state where it is mixed with a polymer other than the protein and / or polysaccharide.

[0045] Next, the mineral particles coated with protein and / or polysaccharide are irradiated with plasma. The mineral particles irradiated with plasma have a surface charge imparted by the plasma, becoming charged particles. In one embodiment, the mineral particles irradiated with plasma are positively charged, specifically, have a surface charge of 0.01 to 1.0 mV, 0.02 to 0.5 mV, or 0.05 to 0.1 mV.

[0046] The plasma irradiation conditions are not limited as long as mineral particles with an appropriate charge can be produced, but irradiation may be performed for 5 to 120 seconds at a high frequency output of 50 to 500 W, and preferably for 10 to 60 seconds at 100 to 300 W. Irradiation with a lower output and for a shorter time may not produce the desired modification effect, while irradiation with a higher output and for a longer time may lead to reduced workability and deterioration of the base material, and is therefore not preferred.

[0047] In one embodiment, the step of irradiating with plasma may be a step of irradiating with plasma in a reducing atmosphere or a substantially vacuum atmosphere. A reducing atmosphere refers to an environment in which there is no oxygen or only a small amount of oxygen, and there is a large amount of reducing gas such as hydrogen or carbon monoxide, or an inert gas such as helium or argon. By preventing oxidation due to plasma irradiation, mineral particles having desired properties can be obtained.

[0048] The term "near vacuum atmosphere" refers to a low vacuum atmosphere, a medium vacuum atmosphere, or a high vacuum atmosphere, and specifically, a vacuum degree of 1×10 -5 Pa~1×10 4 Pa, 1×10 -3 Pa~1×10 3 Pa or 1×10 -1 Pa~1×10 2 The atmosphere may be a vacuum of 100 Pa.

[0049] The plasma is generated by applying a voltage in a reducing atmosphere or a substantially vacuum atmosphere. Specifically, a voltage of several thousand to several tens of thousands of volts is applied in an atmosphere containing a reducing gas or an inert gas to induce an ionization reaction, thereby generating the plasma. In one embodiment, the plasma is generated by applying a voltage of 10,000 to 30,000 volts or 18,000 to 20,000 volts.

[0050] The time for which the mineral particles are exposed to the plasma is not limited, but if the exposure time is too short, the properties imparted by the plasma may be insufficient, and if the exposure time is too long, the protein and / or polysaccharide coated on the surface may be excessively carbonized. In one embodiment, the plasma exposure time is 10 to 40 seconds, and is 20 to 30 seconds.

[0051] One embodiment of the present invention is an organic adsorbent containing mineral particles as an active ingredient, the mineral particles being obtained by irradiating plasma onto mineral particles whose surfaces are coated with proteins and / or polysaccharides. Another embodiment is an organic adsorbent containing mineral particles as an active ingredient, the mineral particles being obtained by irradiating plasma onto mineral particles whose surfaces are coated with proteins and / or polysaccharides so that the surface charge is 0.05 mV to 0.1 mV.

[0052] Another embodiment of the manufacturing method of the present invention includes a step of firing the mineral particles irradiated with plasma. The firing temperature in this step can be 1000° C. to 1500° C., 1050° C. to 1150° C., or 1100° C. This step melts the components in the mineral particles, and can strengthen the structure of the particles.

[0053] Another aspect of the manufacturing method of the present invention includes a step of molding the mineral particles irradiated with plasma. One aspect of this step is a step of mixing the mineral particles with an additive such as a binder, and molding the mixed mineral particles with a press molding machine, an extrusion molding machine, etc. The mineral particles can be molded into a tablet shape, a pellet shape, a chip shape, a disk shape, a block shape, etc. EXAMPLES

[0054] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0055] 1. Preparation of Examples and Comparative Examples An organic adsorbent of the embodiment was manufactured. 70 parts by weight of clinoptilolite, 10 parts by weight of kaolinite, 5 parts by weight of montmorillonite, 2 parts by weight of laumontite, 2 parts by weight of pearlite, 1 part by weight of quartz, 6 parts by weight of pozzolan, 2 parts by weight of makbanite, 0.065 parts by weight of monazite, 0.035 parts by weight of bastnaesite, 0.01 parts by weight of neodymium, and 0.01 parts by weight of dysprosium were mixed and heated to obtain mineral particles. The mineral particles, 0.002 to 0.0033 parts by weight of collagen freeze-dried powder, and the same part by weight of sap, etc. were stirred to coat the surface of the mineral particles with collagen. Furthermore, a voltage of 18,300 V was applied under a reducing atmosphere to generate plasma, and mineral particles with a surface charged to 0.07 mV were obtained. This was fired at 1100 ° C. to obtain an organic adsorbent of the embodiment.

[0056] An organic adsorbent of a comparative example was manufactured. 70 parts by weight of clinoptilolite, 10 parts by weight of kaolinite, 5 parts by weight of montmorillonite, 2 parts by weight of laumontite, 2 parts by weight of perlite, 1 part by weight of quartz, 6 parts by weight of pozzolan, 2 parts by weight of makbanite, 0.1 parts by weight of light rare earth, 0.01 parts by weight of neodymium, and 0.01 parts by weight of dysprosium were mixed and heated to obtain mineral particles. The mineral particles, 0.002 to 0.0033 parts by weight of freeze-dried hemp powder, and the same parts by weight of sap, etc. were stirred. This was fired at 1100 ° C. to obtain an organic adsorbent of a comparative example.

[0057] The surface of the produced organic adsorbent was observed using a scanning electron microscope. As shown in Figure 1, it was confirmed that the surface of the mineral particles was coated with proteins, etc.

[0058] 2. Evaluation of organic matter adsorption capacity of Examples and Comparative Examples The organic matter adsorption capacity of the examples and comparative examples was evaluated. In addition to the above-mentioned mineral particles (Comparative Example 1), commercially available coconut shell activated carbon (Comparative Example 2) was used in the comparative examples. 0.05 g of the examples or comparative examples was added to 400 mL of the test liquid containing a high content of PFAS, and the mixture was shaken at room temperature for 24 hours using a shaker (MW-SRV, manufactured by Miyamoto Riken Kogyo Co., Ltd.), and the examples and comparative examples were removed by filtration through a 0.2 μm membrane filter to obtain a filtrate. Among the PFAS contained in the test liquid and the filtrate, perfluorooctane sulfonic acid (hereinafter referred to as PFOS), perfluorooctanoic acid (hereinafter referred to as PFOA), and perfluorohexane sulfonic acid (hereinafter referred to as PFHxS) were quantified by the method specified in the Japanese Industrial Standard K0450-70-10.

[0059] The test liquid contained 525 μg / L of PFOS, 381 μg / L of PFOA, and 101 μg / L of PFHxS. The following table shows the concentration of each substance in the filtrate obtained by adding the Example or Comparative Example, the adsorption rate of each substance contained in the test liquid, and the adsorption amount per unit weight of the Example and Comparative Example. The Example showed a high adsorption rate of 95% or more for all PFASs, PFOS, PFOA, and PFHxS. The Example was shown to exhibit excellent adsorption ability for all PFASs, compared to Comparative Example 1, which contains mineral particles with a mineral composition similar to that of the Example, and Comparative Example 2, which is a commercially available activated carbon.

[0060] [Table 1]

Claims

1. An organic adsorbent that contains mineral particles as an active ingredient and adsorbs organic fluorine compounds, The mineral particles are composed of one or more selected from clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, monazite, and bastnaesite; the mineral particles include neodymium and dysprosium; the surface of the mineral particles is coated with proteins and / or polysaccharides; The protein and / or polysaccharide is one or more selected from collagen, elastin, a protein containing desmosine or isodesmosine, and a glycosaminoglycan. Organic matter adsorbent.

2. The organic adsorbent according to claim 1 , wherein the organic fluorine compound is a perfluoroalkyl compound or a polyfluoroalkyl compound.

3. 2. The organic adsorbent according to claim 1, wherein the surface charge of the mineral particles is between 0.05 mV and 0.1 mV.

4. The organic adsorbent according to any one of claims 1 to 3, wherein the mineral particles are composed of clinoptilolite, kaolinite, montmorillonite, laumontite, perlite, quartz, pozzolana, makbanite, and monazite and / or bastnaesite.

5. A method for producing the organic adsorbent according to claim 1, comprising the steps of: Providing mineral particles; coating the surface of the mineral particles with proteins and / or polysaccharides; exposing the coated mineral particles to a plasma; Including, The protein and / or polysaccharide is selected from collagen, elastin, a protein containing desmosine or isodesmosine, and a glycosaminoglycan; Manufacturing method.

6. The step of irradiating the plasma is a step of irradiating the plasma in a reducing atmosphere or a substantially vacuum atmosphere. The method according to claim 5 .

Citation Information

Patent Citations

  • JP1973022369B1

  • Water cleaning material

    JP2005262209A

  • Water quality improving treatment agent and method of manufacturing the same

    JP2010012411A

  • Manufacturing method of adsorbent containing fine hydrotalcite

    JP2019136703A

  • Perfluoroalkyl and polyfluoroalkyl adsorbent materials and methods of use

    JP2022526606A